P.E. 1 : physical fitness, self- testing activities - Tulio, Doris D.; Sarmiento, Estelita F.;Battung, Josephine B.;Laggui, Ma. Corazon A.;Bumagat, Noel R. (Makati City, Philippines : Katha Publishing Co, Inc., 2005)
Physical education is the part of the school curriculum that instructs the students in body movements, sports, and games and other physical activities.
Unit 1 Physical education : its values to the development and adjustment of the individual -- Unit 2 Physical fitness and testing -- Unit 3 Warm-up conditioning exercises -- Unit 4 Aerobic dance for health and fitness -- Unit 5 Improving physical fitness : strength, flexibility, agility and balance -- Unit 6 Group games for fitness.
Includes bibliographical references.
Keywords: PHYSICAL EDUCATION AND TRAINING -- STUDY AND TEACHING